Predictors and Moderators of Parent Engagement in Early Interventions for Behaviorally Inhibited Preschool-Aged Children. Issue 4 (1st October 2020) - Novick, Danielle R.; Smith, Kelly A.; Barstead, Matthew G.; Danko, Christina M.; Rubin, Kenneth H.; Druskin, Lindsay; Badders, Rebekah N.; Dougherty, Lea; Chronis-Tuscano, Andrea
ABSTRACT: Behavioral inhibition (BI) is a temperamental style that poses risk for later anxiety. Efficacious interventions have been developed for inhibited children, but their success depends on parent engagement. However, little is known regarding predictors of parent engagement in early interventions for BI. This study examined parent-, child- and treatment-level (i.e., parent-only or parent-child) factors as independent and interactive predictors of parent engagement (attendance, and parent-reported homework completion and treatment satisfaction) in a randomized-controlled trial comparing two interventions for inhibited preschoolers: Cool Little Kids (CLK) and the Turtle Program ("Turtle"). We also explored predictors of co-parent (CP) attendance. The sample comprised 151 primary parents (PPs) and their 45–64-month-old children. Attendance was greater in Turtle and homework completion was slightly greater in CLK, with no group difference in satisfaction. In Turtle, child anxiety predicted greater PP attendance and PP depression predicted lower satisfaction. In CLK, the interaction between child and PP anxiety significantly predicted satisfaction. Across groups, child anxiety predicted greater homework completion and CP anxiety predicted greater CP attendance. Results suggest that child anxiety may motivate parent engagement, particularly when children receive concurrent treatment and/or in-vivo coaching. However, intensive treatment may be too burdensome for depressed parents, whereas less intensive treatments may be more acceptable to non-anxious parents of anxious children. These findings can inform approaches to improve parent engagement in early interventions targeting BI.